Experimental study on light weight panel using phosphogypsum. (2022) - Muthukumar, P.; Shewale, Manisha; Asalkar, Shraddha; Shinde, Nitin; Korke, Pavankumar; Anitha, M.; Gobinath, R.; Anuradha, R.
Abstract: Recent splurge in the civil engineering industry is fuelled by the growth of industrial clusters across nation and also by conversion of villages into towns and cities. The technological developments and changes are results of industrial growth which resulted in tremendous use of natural resources as a raw material and mass production of manufacturing goods. The development of new technologies and their use in industry also effected the non-industrial sectors. Agriculture sector is also influenced by the industrial growth, with the advent of newer processing technologies it grown manifold. Surging population had put thrust on more production of agricultural produce, the production ended up only with huge amount of waste materials and by products. Among those materials Phosphate is one valuable material which is a nutrient that is very essential for the survival of plants and animal, this is derived from Phosphate rock. Phosphate rock is converted into fertilizer through industrial process, and it is being used widely for agricultural purpose. Also, phosphate is used in many products that produces wastes including phosphogypsum which is generated as waste from phosphate industry. This waste is discharged in sea, rivers and other water courses which has huge adverse effects on ecological system and human life. Much research is carried out to reuse the waste products for making sustainable goods and reduce the problem of disposal. In construction industry, phosphogypsum can be used in concrete. In this work, an attempt is made to utilise waste phosphogypsum in concrete that is widely used construction material to produce light weight panels for industrial and residential purpose. Thrust is given to understand the strength and durability characters of the produced composite so that its industrial usage can be defined. Promising results were obtained with decent increasing in strength and durability which shows that the material can be used effectively in Civil engineering industry.